Budaya Patriarki dalam Rumah Tangga (Pemahaman Teks Al-Qur’an dan Kesetaraan Gender) - Mochomad Nadif Nasruloh; Taufiq Hidayat (Program Studi Hukum Keluarga Islam, 2022)
Patriarchy is a perspective that places men as superior over women. The problem lies in understanding the Qur'an Surah An-Nisa 4:34 which causes discriminatory-patriarchal treatment of wives. This article aims to answer 2 (two) main questions. First, about the implications of understanding the text of the Qur'an on patriarchal culture in the household. Second, regarding the meaning of Surah an-Nisa verse 34 in the discourse on the equality of husband and wife. Methodologically, this article uses a qualitative article method with literature study and content analysis techniques. The findings in this article, firstly, the interpretation of classical interpretations strengthen patriarchal culture and give legitimacy to husbands to force their wives to take on the role of domestic workers and only focus on three things, namely wells, mattresses and kitchens. Second, the husband's leadership in the household is not leadership that makes the husband authoritarian, but in the form of leadership that provides protection to his wife. There is no superior and no inferior party.Patriarki merupakan cara pandang yang menempatkan lelaki sebagai lebih utama (superior) di atas perempuan. Persoalannya terletak pada pemahaman terhadap Al-Qur’an Surat An-Nisa 4:34 yang menimbulkan perlakuan diskriminatif-patriarkis terhadap istri. Artikel ini bertujuan untuk menjawab 2 (dua) persoalan utama. Pertama, tentang implikasi pemahaman teks Al-Qur’an terhadap budaya patriarki dalam rumah tangga. Kedua, tentang pemaknaan Surat An-Nisa ayat 34 dalam diskursus kesetaraan suami istri. Secara metodologis, artikel ini menggunakan metode artikel kualitatif dengan studi kepustakaan serta teknik analisis isi. Adapun hasil temuan dalam artikel ini, pertama, corak penafsiran tafsir klasik mengokohkan budaya patriarki dan memberikan legitimasi kepada suami untuk memaksa istri mengambil peran sebagai pekerja domestik dan hanya berkutat pada tiga hal, yakni sumur, kasur dan dapur. Kedua, kepemimpinan suami dalam rumah tangga bukanlah kepemimpinan yang menjadikan suami bersikap otoriter, namun berupa kepimpinan yang memberikan pengayoman kepada istrinya. Tidak ada pihak yang superior dan tidak ada pula pihak yang inferior.